Determination of various parameters of sexual maturity in adolescent boys in Ankara - Kınık, Erol; Karaman, Özkan; Büyükgebiz, Atilla (The Turkish Journal of Pediatrics, 1987)
879 male adolescents between 11-19 years of age were investigated with respect to testicular length, testicular volume, pubic hair stages, and chronologic and skeletal ages. In pubic hair Stage 1, the mean testicular volume was found to be 3.11 ± 1.70 ml and the largest testicular volume increase was observed between pubic hair Stages 3 and 4. In pubic hair Stage 5, the mean testicular volume was 22.27 ± 4.55 ml. Pubic hair became visible at a mean chronologic age of 12.04 ± 1.74 and a mean skeletal age of 11.28 ± 1.74 . The subjects reached PH 5 at a mean chronologic age of 15.97 ± 3.15 and a mean skeletal age of 16.41 ± 3.00 . Our results were compared with those in the literature.